RANCANG BANGUN WEBSITE UNTUK MEDIA PROMOSI PADA UMKM KUNYAHAN MEDAN - Ranggi Marantika; Khaliq, Abdul; Hardiansyah Putra (Jurnal Nasional Teknologi Komputer, 2025)
The rapid advancement of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital media as an effective promotional strategy. Kunyahan Medan MSME, which specializes in producing traditional Medan snacks, still relies on promotions through bazaars, hotels, and social media, without an official website that could expand its market reach digitally. This study aims to design and develop a promotional website using Laravel and MySQL, applying the Waterfall methodology. The web development stages include requirements analysis, system design, implementation, testing, and maintenance. The website is built with two user roles: visitors and administrators. Key features include a product list, product details, contact page, and WhatsApp chatbot integration to facilitate direct communication with customers. Testing using the Blackbox method showed that all features functioned properly and were responsive across various devices. This study demonstrates that website development using the Waterfall method can be an effective and efficient solution to support digital promotion for MSMEs, contribute to expanding digital market reach, improve the quality of delivered information, and provide a better digital interaction experience for customers.